IMPLEMENTASI TAX AMNESTY DI KALIMANTAN TIMUR - Sarwo Eddi Wibowo (LPPM University 17 Agustus 1945 Samarinda, 2018)
This study aims to determine the social-economic changes of the poor community after the acceptance of the business capital assistance program, to develop the tax potential and tax ratio realization for the realization of participation, community responsibility and independence in development.The results showed that the implementation of tax amnesty in the form of national tax reform is to further enforce the independence of the State in financing national development by way of more directed all the capabilities / potential of the taxpayer community.